Versions of a Feminine Voice: The Compiuta Donzella di Firenze*. (2nd January 2018) - Bowe, David
Abstract: This article offers a detailed reading of the surviving sonnets of the poet known as the Compiuta Donzella di Firenze, paying particular attention to her performance of a feminine subject and critical engagement with common lyric tropes. A lack of biographical information about the Compiuta Donzella, the first woman to whom literary texts in the Italian vernacular are attributed, has led to speculation over her identity and 'authenticity', or to biographical readings of her texts. Acknowledging the same sorts of playful, ironic, and performative lyric subject and content in the Compiuta Donzella's work that are commonly ascribed to other lyric voices allows us to appreciate the technical and thematic artifice in her sonnets. Comparative close readings of her surviving texts and some responses to them (by Guittone d'Arezzo, Maestro Rinuccino or Guido Guinizzelli, and an anonymous poet) provides a broader perspective on her work as engaged in active dialogue with the lyric context of thirteenth-century Italy.